Pessimistic prospects of the scientific worldview: a potential Islamic defense for the future leadership of Muslim youths - Ali, Mohd Mumtaz; Hasan, Md Maruf (Semarak Ilmu Publishing, 2024)
This research paper tries to deal with contemporary concerns of the scientific worldview.In the past, pessimism from the scientific worldview was just a mere dichotomy between Western secular intellectuals and Christian authority as we have learned from the Western history. However, Salaman Rushdi and Ibn Warraq indicated something different. The scientific worldview may affect the attitudes of Muslim youths. After the fall of the Arab spring, Islamic movements may face difficulties in Muslim societies. What went wrong with the Mursi regime when he was elected following Western democracy? This research paved an alternative way to understand the difficulties of Islamic movements. Then, the article tried to provide a feasible solution for the future leadership of Muslim youths. This research also looked into the works of Imam Ghazali, Muhammad Iqbal and Sayyid Qutub for the possible solution against pessimism of the scientific worldview. This article used qualitative methodology. The research found that despite having the dominancy of the scientific worldview in the 21st century, Islam has a unique way of dealing with the pessimistic politics of the scientific worldview. Machiavelli’s notion of Lion and Fox and Nietzsche’s master and slave morality have been explored to understand the problem with contemporary Islamic movements. In addition, the article suggested that Imam Ghazali, Muhammad Iqbal and Sayyid Qutub were able to draw some defense mechanisms against the scientific worldview.